Impact of COVID-19 on maternal and perinatal outcomes in Harare, Zimbabwe: a comparative maternal audit - Yemurai Bikwa; Grant Murewanhema; Mufaro Kanyangarara; Mugove G Madziyire; Zvavahera M Chirenje (Journal of Global Health Reports)
# Background